Identification of radiation induced mutants of cassava (Manihot esculenta Crantz) using morphological and physicochemical descriptors - Tofino, A; Cabal, D.; Sánchez, T.; Ceballos, H. (2011)
For mutants of starch and other desirable traits of interest in cassava, we evaluated the physical-chemical morphology of the root and paste in inbred populations of six M2 families, derived from irradiated seeds. 1,097 plants were established, 829 of Gamma treatment and 268 of neutrons. In the morphological description, most chimeras recorded in M1 were identified except hermaphrodite flowers and bark of different colors on the same plant, new abnormalities in M2 were found, such as root without suberification, no anthesis, early flowering, meristems and changes in the supply-demand relationship. However, mortality, reduced vigor, yield and anthesis loss have also been identified as effects of inbreeding. Simple techniques such as optical microscopy and iodine staining were effective for the identification of mutants of the granule and the results were confirmed with electron microscopy analysis and pulp properties, except in mutant granule hole, in which no abnormalities of the granule were correlated with significant variations in the paste. However, Pearson correlations associated the hot paste viscosity with consistency and reorganization. Variability was found in the granule characteristics and properties of the paste between years, suggesting significant influence of genotype-environment interaction. Similarly, there were differences in paste properties associated with the type of radiation. In addition, promising mutants were identified with post-harvest physiological deterioration tolerance associated mainly to gamma.